The Good Governance Principles Implementation in Public Sector Services at Dinas Pendidikan Kota Bandung - Thoriq Abdul Aziz; Idrus Affandi; Muhammad Halimi (Jurnal Civicus, 2020)
The implementation of good governance principles is an important aspect of public sector services in government institutions. The policy of implementing the good governance principle in public service has been found in implementing one-roof service policies methods integrated into by Dinas Pendidikan Kota Bandung. This research approach is qualitative with case study methods. Data collection techniques use interviews, observation, and documentary studies. The participants of this research are the head and staff of Bagian Umum dan Kepegawaian, and the public service community of teachers and school staff. The results of this research are (1) a one-stop-shop public sector service was a way of improving the quality of good governance public services; (2) the principle of good governance as applied are accountable, accountable, effective and efficient; (3) communities using public services feel a service barrier from aspects of service effectiveness and efficiency, and employees respond while performing public service; (4) efforts made by the Dinas Pendidikan Kota Bandung will be the socialization of a massive public service procedure and assessments of one-roof service policies by reviewing the good governance indicators used in public sector service in Dinas Pendidikan Kota Bandung.